Some Factors Affecting on Magnetic Characteristic Quantities and Tc Curie Phase Transition Temperature of the Ni Nanoparticles by the Classical Heisenberg Model - Trong Dung, Nguyen; Khac Hung, Pham (International Journal of Engineering and Technology, 2018)
Â This paper investigates the effect of particle size D = 4.51nm, 5.03nm, 5.42nm, 5.91nm, rate of heat 4.1012K/s, 4.1013K/s, 4.1014K/s on magnetic characteristic quantities: Magnetization M, specific heat Cv, energy E, magnetic susceptibility c and Tc Curie phase transition temperature by classical Heisenberg model. The results show when increasing D particle size then Tc Curie transition temperature increases and when increasing rate of heat then Tc decreasing. In addition, there is the influence of D size and heating rate on magnetic characteristic quantities.Â Â